Effects of Polypropylene Waste Addition as Coarse Aggregates in Concrete: Experimental Characterization and Statistical Analysis. (8th November 2022) - Naveen, D. C.; Naresh, K.; Keerthi Gowda, B. S.; Reddy G, Madhu Sudana; Prasad, C. Durga; Shanmugam, Ragavanantham
Abstract : In recent times, thermoplastic waste materials are being extensively used as fine and coarse aggregates in the concrete mix as an environmentally friendly construction material. This study aims at utilizing polypropylene (PP) as a partial substitute for the conventional coarse aggregates in M30 grade concrete. The different replacement levels of coarse aggregates such as 0%, 20%, 40%, and 60% by weight were used in concrete. Sieve analysis, specific gravity, and water absorption tests were performed in all replacement levels of aggregates. The mechanical (compressive and split tensile tests) tests were conducted after 3, 14, and 28 days. The change in mechanical properties of concrete with the addition of different weight proportions of plastics was studied experimentally. Further, experimental values were predicted using the two-parameter Weibull distribution and artificial neural network (ANN)-based statistical approaches. The Levenberg–Marquardt algorithm was used in predicting the mechanical properties using the ANN. A good correlation was obtained between the experimental and predicted values with an error (%) of less than 10. The decrease in mechanical properties with the increase in replacement levels of coarse aggregates in concrete was observed in both experimental and predicted approaches. This can be attributed to poor bonding between concrete and PP aggregate owing to the development of agglomerations and the hydrophobic nature of PP. However, the strength values of 20% PP-embedded concrete specimens are closer to 0% PP-embedded concrete specimens. Therefore, 20% PP-embedded concrete specimens can be used for primary load-bearing applications to utilize plastic waste and reduce the cost of the component.